Neuroprotective Properties of Xenon According to Experimental Studies - O. A. Grebenchikov; I. V. Molchanov; A. I. Shpichko; A. K. Yevseyev; A. K. Shabanov; S. Z. Khusainov; S. S. Petrikov (Неотложная медицинская помощь, 2020)
ABSTRACT. An increase in the number of patients with severe brain damage of various etiologies determines the need to improve neuroprotection technologies. The review is devoted to modern views on the mechanisms of brain protection, as well as the basic processes underlying damage to neurons. The article discusses the results of the most important experimental studies in this area using inert xenon gas. The authors analyzed a number of works highlighting neurotective properties of the xenon inhalation anesthetic in studies performed in vitro and in vivo. The main mechanisms of neuronal death depending on the type of damage are shown, the points of application of the protective effect of xenon on the brain and the prospects for further research in this area are demonstrated in the article.